2003
DOI: 10.1515/cclm.2003.180
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxal and Methylglyoxal Levels in Diabetic Patients: Quantitative Determination by a New GC/MS Method

Abstract: Determination of glyoxal and methylglyoxal levels in plasma is of great interest, since it allows us to evaluate oxidation processes occurring in glycated proteins. A method based on a simple derivatization procedure followed by gas chromatography/mass spectrometry (GC/MS) analysis has been developed. Ten diabetic patients were evaluated before and after improvement of glycemic control. Fasting plasma glucose, hemoglobin A1c (HbA1c), advanced glycation end products (AGE), pentosidine, glyoxal and methylglyoxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
181
1
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(194 citation statements)
references
References 25 publications
6
181
1
6
Order By: Relevance
“…One of the pathologies of this disease is sustained hyperglycemia. As MG concentrations in plasma of diabetic patients are higher than those in healthy individuals (11)(12)(13), MG may inhibit GLUT1 constitutively expressed on the plasma membrane of many tissues, thereby lowering the efficacy of glucose uptake, which exacerbates the hyperglycemia. In addition, we have shown that MG inhibits GLUT4 also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the pathologies of this disease is sustained hyperglycemia. As MG concentrations in plasma of diabetic patients are higher than those in healthy individuals (11)(12)(13), MG may inhibit GLUT1 constitutively expressed on the plasma membrane of many tissues, thereby lowering the efficacy of glucose uptake, which exacerbates the hyperglycemia. In addition, we have shown that MG inhibits GLUT4 also.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MG levels and diabetic complications are closely related (10). The levels of MG in blood and tissues are higher in diabetic patients than healthy individuals (11)(12)(13). However, it remains to be solved whether high MG levels are a cause or a consequence of diabetes.…”
mentioning
confidence: 99%
“…Arg 10 , Arg 33 , and Arg 85 , in addition to Arg 39 , and that their distribution among the arginine residues might be uneven. We therefore searched for ions with calculated m/z values of the different charge states of the predicted peptides, 8 10 and Arg 85 modified to G-DH and G-H, were located by extracting ion chromatograms from the full-scan data, thus establishing the formation of both of these adducts at Arg 10 and Arg 85 . When the 7-day 1 mM glyoxal reaction was incu- bated with HA, the kinetics of loss of peptides containing Arg 10 and Arg 85 modified to G-DH/CMA were similar to those of peptide 38 D-K 61 with Arg 39 modified to G-DH, indicating that G-DH and not CMA was also the major or sole adduct on these arginine residues.…”
Section: Site Specificity and Kinetics Of Formation Of G-dh And G-h Amentioning
confidence: 99%
“…Plasma glyoxal levels are much lower than those of glucose, but glyoxal is a far more reactive carbonyl compound. Normal plasma levels of glyoxal are reported to be 215-230 nM (6 -8) but increase to 350 -470 nM in diabetic subjects (7,8), ϳ400 nM in uraemia (6), and ϳ760 nM in end-stage renal disease (6). Because of its high reactivity, the fraction of glyoxal bound to proteins may significantly exceed the measured glyoxal concentration in plasma.…”
mentioning
confidence: 99%
“…Portanto, a geração destes compostos parece ocorrer independentemente da presença de hiperglicemia (Odani et al, 1999;Lapolla et al, 2003). Na doença renal crônica, por exemplo, prevalecem falhas de destoxificação, devido à falência da função renal.…”
Section: Descritorsunclassified